Polyimides from an asymmetric hydroxyl‐containing aliphatic‐aromatic diamine synthesized via henry reaction. Issue 20 (27th July 2017) - Wang, Zhiang; Guo, Liying; Han, Songyu; Qi, Haixia; Cheng, Yusheng; Liu, Feng
ABSTRACT: An aliphatic amino and an aliphatic hydroxyl group have been incorporated via Henry reaction highly efficiently toward the synthesis of a novel asymmetric aliphatic–aromatic diamine 2‐amino‐1‐[4‐(5‐aminopyridyloxy)phenyl]‐1‐ethanol (AAPy Ph E) in three steps. AAPy Ph E shows good copolymerization reactivity with 4, 4′‐oxydianiline (ODA) toward different aromatic dianhydrides, especially 4, 4′‐oxydiphthalic anhydride (ODPA). TGA measurement and mechanical test results show that all polymers maintain the inherent thermal performance and tensile properties, while the glass transition temperatures ( T g 's) by DMA show moderate decrease ranging from 185.5 to 253.3 °C due to the presence of aliphatic segments. The introduction of AAPy Ph E is found to improve the solubility of the polymers, and the polymer films' optical transparency with decreased cutoff wavelength ( λ 0 ) ranging from 328 to 370 nm. Comparative studies reveal that the pendent aliphatic hydroxyls in the polymer chains would lead to interchain cross‐linking via condensation and secondary weak cross‐linking by hydrogen bond depending on different loading of AAPy Ph E, which result in a fluctuation of hydrophilic–hydrophobic properties, DMA tan δ and dielectric constant of the copolymer films. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3413–3423 Abstract : An asymmetric aliphatic hydroxyl‐containing aliphatic–aromatic diamine prepared via Henry reaction shows sufficient polymerization reactivity with the dianhydride ODPA toward the synthesis of polyimide and copolyimde with ODA. Depending on different loading, the aliphatic hydroxyls play an important role in forming different type of polymer interchain structures including cross‐linking via condensation or via hydrogen bond, which impacts the surface hydrophilic–hydrophobic, DMA tan δ, and dielectric properties of the copolymer films in fluctuated manners.